2017
DOI: 10.1094/phyto-04-16-0170-r
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of Two Quantitative Trait Loci for Type II Resistance to Fusarium Head Blight in Wheat Germplasm PI 672538

Abstract: Fusarium head blight (FHB), mainly caused by Fusarium graminearum, is a destructive disease in wheat. A population consisting of 229 F and F plants derived from the cross PI 672538 × L661 was used to evaluate the reactions to FHB. The FHB resistance data distribution in the F population indicates that some quantitative trait loci (QTLs) were controlling the FHB resistance in PI 672538. We further detected two major QTLs (Qfhs-2B, Qfhs-3B) from analysis of the resistance data and the PCR-amplified results using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…We found that L693 exhibited a high level of FHB resistance [ 20 ]; only the inoculated spikelet had dried out and died at 21 days after inoculation (DAI) with F. graminearum . By contrast, in L661, after the same period of time, almost the entire spike containing the inoculated spikelet had dried out and died ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that L693 exhibited a high level of FHB resistance [ 20 ]; only the inoculated spikelet had dried out and died at 21 days after inoculation (DAI) with F. graminearum . By contrast, in L661, after the same period of time, almost the entire spike containing the inoculated spikelet had dried out and died ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of 12 samples showed that the greatest difference in gene expression following F. graminearum infection occurred between different tissues (spike vs. leaf), while the smallest difference was observed between the resistant and susceptible genotypes ( Figure 3 B). This could be due to the fact that L693 and L661 have similar genetic backgrounds [ 16 , 20 , 23 ]. The fact that the greatest difference in gene expression occurred between the spike and leaf indicated that the transcriptome data were reliable to some degree, which could be a real response after F. graminearum infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusarium head blight (FHB), mainly caused by Fusarium graminearum Schwabe and F. culmorum WG Smith, is a serious wheat (Triticum aestivum L.) disease worldwide (Bai & Shaner 2004;Li et al 2017). In China, FHB epidemics have frequently occurred in the middle to lower valleys of the Yangtze River (Yao & Lu 2000).…”
Section: Abstract: Agronomic Trait; Fhb; Resistance Evaluation; Tritimentioning
confidence: 99%
“…From agronomical traits and application standpoints of view, we developed the following four spring wheat lines: L658 (PI 672537), L693 (PI 672538), L696 (PI 672539), and L699 (PI 672540). These lines exhibited excellent agronomic traits, including yield and resistance to Fusarium head blight conferred by FhbL693a and FhbL693b [ 24 ], to stripe rust conferred by YrL693 [ 25 ] and to powdery mildew conferred by Pm40 [ 22 , 23 , 26 , 27 ]. Though the pedigree of PI 672538 includes Th .…”
Section: Introductionmentioning
confidence: 99%